The Role of Middle Managers in Enhancing Safety at a Power Plant - Christensen,Karsten Bach (2025)
The thesis examines the role of middle managers in improving safety at a power plant. Through a social constructivist approach, it analyses how middle managers can shape and sustain safety through their communication, attitudes, and actions. The study focuses on the challenges middle managers face in balancing leadership duties, administrative responsibilities, and their own tasks, often at the expense of proactive safety management. A qualitative methodology is employed, using semi-structured interviews and focus group discussions to gather data from middle managers and employees. The data is analysed through a narrative analytical approach. The thesis concludes that middle managers play a central role in creating and maintaining a safety at a power plant. Their ability to navigate complex leadership paradoxes and integrate safety into daily operations is vital for ensuring sustainable safety practices. A more systematic approach to learning and better integration of safety into the organisation’s strategic management are needed to further enhance safety.
Keywords: Middel managers; Leaders; Sensemaking; Safety; Communication; Leadership; Narratives; Production; Cognitive dissonance; FLMU06